Cover Image, Volume 180B, Number 2, March 2019. Issue 2 (21st February 2019) - Budde, Monika; Anderson‐Schmidt, Heike; Gade, Katrin; Reich‐Erkelenz, Daniela; Adorjan, Kristina; Kalman, Janos L.; Senner, Fanny; Papiol, Sergi; Andlauer, Till F. M.; Comes, Ashley L.; Schulte, Eva C.; Klöhn‐Saghatolislam, Farah; et al.
Abstract : The cover image is based on the Research Article A longitudinal approach to biological psychiatric research: The PsyCourse study by Monika Budde et al., DOI: 10.1002/ajmg.b.32639 .